The New Accountability : Environmental Responsibility Across Borders. - Mason, M. (Michael) (Taylor and Francis, 2012)
The growth of pollution that crosses national borders represents a significant threat to human health and ecological sustainability. Various international agreements exist between countries to reduce risks to their populations, however there is often a mismatch between national territories of state responsibility and transboundary hazards. All too often, state priorities do not correspond to the priorities of the people affected by pollution, who often have little recourse against major polluters, particularly transnational corporations operating across national boundaries. Drawing on case stu.